Effects of kinesio taping on lower limb biomechanical characteristics during dynamic postural control tasks in individuals with chronic ankle instability - Tao Yuan; Haixia Li; Guanglan Wang (PLoS ONE, 2025)
Purpose Previous studies have demonstrated significant biomechanical differences between individuals with chronic ankle instability (CAI) and healthy controls during the Y-balance test. This study aimed to examine the effects of kinesio taping (KT) on lower limb biomechanical characteristics during the Y-balance anterior reach task in individuals with CAI. Methods A total of 30 participants were recruited, comprising 15 individuals with CAI and 15 healthy controls. All participants were randomly assigned three taping conditions: no taping (NT), placebo taping (PT), and KT, followed by the Y-balance anterior reach task. Each condition was separated by one-week intervals. Kinematic and kinetic data of the lower limbs during the movement phase were collected using the Vicon motion capture system (Vicon, T40, 200 Hz) and two Kistler force platforms (Kistler, 1000 Hz). Results KT significantly improved the Y-balance anterior reach distance (P = 0.003) and peak ankle eversion angle (P = 0.019) compared to NT. Additionally, KT resulted in increased peak knee flexion angle (P = 0.002, P = 0.011) and peak ankle dorsiflexion angle (P <0.001, P = 0.005) relative to both NT and PT. KT also significantly reduced mediolateral center of pressure (COP) displacement (P = 0.001) and average velocity of mediolateral COP displacement (P = 0.033) in comparison to NT. Furthermore, KT decreased mediolateral center of gravity displacement (P = 0.002, P = 0.003) relative to both NT and PT. Conclusion KT significantly improved abnormal ankle posture by promoting greater ankle dorsiflexion and eversion angles. Additionally, KT reduced mediolateral COP displacement and average velocity to improve postural stability. These changes may contribute to reduced risk of ankle sprains. Therefore, KT may serve as an effective tool for managing recurrent ankle sprains in individuals with CAI.